Modified Smith predictor‐based all‐proportional‐derivative control for second‐order delay‐dominated integrating processes. Issue 2 (10th November 2020) - Karan, Somak; Dey, Chanchal
Abstract: An all‐proportional‐derivative (PD) control‐based modified Smith predictor design is reported here for second‐order delay‐dominated integrating processes. The proposed control structure is realized with two PD controllers along with a first‐order filter towards achieving the desired closed‐loop response. To eliminate the tuning complexity, reported internal model control (IMC) scheme suggests a single tuning parameter λ (i.e. closed‐loop time constant) to tune both the PD controllers along with the filter present in the modified Smith predictor designing. The forward path PD controller parameters are obtained as per the IMC tuning guideline suggested for servo tracking, whereas the feedback path PD controller is realized based on Routh stability analysis with a goal towards improved regulatory responses. The first‐order filter present in the feedback path helps to ensure robust closed‐loop performance. Considerable performance enhancement is observed during set point tracking by the proposed scheme where no overshoot is observed even with smaller rise time. In addition, smooth and reasonably quick load rejection behaviour is also found during a regulatory response. Superiority of the proposed scheme is also substantiated in comparison with others' reported dead‐time compensating techniques in terms of closed‐loop performance indices as well as stability margins.